REPAIR PLANNING FOR THE RUNWAY OF TORAJA AIRPORT BASED ON THE RESULTS OF FLEXIBLE PAVEMENT DAMAGE ANALYSIS WITH THE PAVEMENT CONDITION INDEX (PCI) METHOD ASTM D5340-98 - Agustin, Wahyu Shesar; Winiasri, Linda; Triyono, Agus (Jurnal Disprotek, 2025)
The runway is one of the airport airside facilities that plays a crucial role in the safety and comfort of flight operations. The condition of the runway needs to be monitored for pavement feasibility so as not to interfere with the movement of aircraft. In maintaining pavement feasibility, maintenance and repair planning are required. Maintenance and repair planning must be adjusted to the needs of handling damage that occurs. Pavement Condition Index (PCI) is one of the methods commonly used in analyzing pavement damage. Through the results of the PCI, appropriate maintenance and repair planning can be determined for damage to the passenger parking area. The method used is visual observation of the Pavement Condition Index (PCI) based on ASTM D5340-98. The result of this research is that the runway area of Toraja Airport obtained a PCI value of 43.75. Damage that occurs includes local decline (depression) and weathering and loose grains (weathering and raveling). Based on Regulation of the Director General of Civil Aviation Number: KP 94 of 2015, in low-damage conditions, maintenance that can be done is to conduct routine inspections and local cleaning. In weathering and raveling damage conditions with medium to high damage levels, but in a small area, local cutting (patching) is required in the area around the damage. In the condition of weathering and raveling damage with medium to high damage levels and large dimensions, the repair carried out is an overlay by carrying out prior maintenance on the existing coating.